SYNONYMY OF PUNCTUATION AND POETIC TEXT (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article presents unusual tasks and examples of the use of punctuation marks in today's modern Uzbek literature. In particular, the phenomenon of synonymy between punctuation marks and its artistic functions in the poetic text are highlighted.